G423(P) Uncommon presentation of septo-optic dysplasia. (25th October 2020) - Jeyaraman, A; Brew, C; Mathew, V; Gupta, S
Abstract : Introduction: Neonatal metabolic acidosis is a common presentation of wide range of causes varying from sepsis to rare metabolic and endocrine problems. Metabolic acidosis with normal anion gap help as to narrow down the cause as GI loss, RTA or adrenal insufficiency. We present a rare case of neonatal metabolic acidosis turned out to be due to adrenal insufficiency and subsequently diagnosed as SOD. Septo-optic dysplasia (SOD) is a rare congenital malformation syndrome characterised by a triad of optic nerve hypoplasia, midbrain abnormality and pituitary dysfunction. Case Report: 19 day-old girl baby presented with lethargy, poor feeding and poor weight gain. On examination, she was hypothermic, hypoglycaemic, hyperkalaemia with early shock and metabolic acidosis. She was treated as presumed sepsis with dextrose, fluid bolus and antibiotics. She had persistent metabolic acidosis with normal anion gap despite on full feeds. Her septic screening and initial metabolic screening were negative. She was noted to have adrenal insufficiency (cortisol <50 ), which was confirmed by synacthen test. Her cranial ultrasound was normal. She was sent home with steroid supplements. She was noticed as not fixing and following with roving eye movements at the age of 4 months. Found to have bilateral optic nerve dysplasia and later registered as blind. Further imaging of MRI head confirmed SOD with underdevelopment of optic nerve and hypoplasia of pituitary gland. She failed the dynamic growth hormone stimulation test. In view of her slow growth and low IGF, she was started on growth hormone treatment. She also has hypothyroidism on thyroxin supplements. She is making good progress in her growth and development with hormone supplements and MDT management. Conclusion: Clinical followed by hormonal evaluation and imaging can guide us to its appropriate diagnosis and treatment of SOD. Early recognition of SOD is paramount in order to reduce morbidity and to optimise management. Without adequate treatment, panhypopituitism can have devastating effects on growth and neurodevelopment of children.